UJI PEMBERIAN LEGIN DAN PUPUK K TERHADAP PERTUMBUHAN TANAMAN KEDELAI (Glycine max (L.) Merrill) PADA KONDISI CEKAMAN NaCl - Bambang Pujiasmanto; Sumiyati Sumiyati; Hery Widijanto; Alfiatun NM (Faculty of Agriculture, Universitas Sebelas Maret, 2010)
Title : Study of Legin and Potassium Fertilizer on Growth of Soybean (Glycine max (L.) Merrill) Under Different NaCl Stress. The research purposed to study the effectively of legin and potassium fertilizer under different NaCl stress on growth of soybean (Glycine max (L.) Merrill). An experimental research 2 X 3 X 4 was held with split-split plot design. The first factor was legin as main factor consisted of without legin (L0) and with legin (L1), the second factor was NaCl concentration as sub factor consisted of 0 mM (S0), 30 mM (S1), 60 mM (S2) and the third factor was ZK potassium fertilizer dosages as sub–sub factors consisted of 0 kg/ha (K0), 25 kg/ha (K1), 50 kg/ha (K2), 100 kg/ha (K3). Thus the number of combinations was 24, then 3 replicates was carried out for every combination. The variables are height of plant, chlorophyll content, total area of leaves, fresh weight of shoot, dry weight of shoot, shoot-root ratio, length of root, and N content of plant. The obtained data were analyzed using analysis of variance procedure at 5% level, if showed significant continued by 5 % of Duncan’s Multiple Range Test (DMRT) and regression analysis. The result showed that NaCl concentration decreased total area of leaves. The highest mean was 573.95 cm2 at NaCl concentration 0 mM and the lowest mean was 421.34 cm2 at NaCl concentration 60 mM. Legin decreased the shoot-root ratio at 2 WAP (Week after Planting); the means are 18.41 at without legin and 10.04 at with legin. ZK potassium fertilizer increased total area of leaves and dry weight of shoot. ZK potassium fertilizer that increased the total area of leaves is 25 kg/ha, while at dry weight of shoot is 50 kg/ha. Interaction between legin and ZK potassium fertilizer held at total area of leaves and N content of plant. Interaction between NaCl concentration and ZK potassium fertilizer held at height of plant, total area of leaves, and shoot-root ratio. Interaction between three factors held at height of plant, total area of leaves and N content of plant. The highest dry weight of shoot 3.35 g at with legin, NaCl concentration 60 mM, ZK potassium fertilizer 50 kg/ha and the lowest 1.41 g at without legin, NaCl concentration 30 mM, ZK potassium fertilizer 0 kg/ha. Keywords: legin, NaCl stress, potassium fertilizer, soybean